RETRACTION Carmona-Espejo, A., & González-Villén, R. (2022). Terapia rehabilitadora en unidades de cuidados intensivos. Revision sistemática (Rehabilitation therapy in intensive care units. Systematic review),. Retos, 46, 758–766. https://doi.org/10.47197/retos.v46.94086 - RETOS, RETOS (Retos, 2025)
Carmona-Espejo, A., & González-Villén, R. (2022). Terapia rehabilitadora en unidades de cuidados intensivos. Revision sistemática (Rehabilitation therapy in intensive care units. Systematic review). Retos, 46, 758–766. https://doi.org/10.47197/retos.v46.94086 Retraction of the article by the editor of the journal. Failure to comply with the obligation to pay the fee once accepted for publication.